LNC-ZNF33B-2:1 gene rs579501 polymorphism is associated with organ dysfunction and death risk in pediatric sepsis - Lu, Zhaoliang; Yu, Hongyan; Xu, Yufen; Chen, Kaining; Lin, Yueling; Lin, Kun; Wang, Yishuai; Xu, Kaixiong; Fu, Lanyan; Li, Weizhan; Zhou, Huazhong; Wei, Bing; et al. (Frontiers in Genetics, 2022)
Background: Sepsis is a severe systemic reaction disease induced by bacteria and virus invading in bloodstream and causing multiple systemic organ dysfunction subsequently. For example, the kidney may stop producing urine, or lung may stop taking in oxygen. Recent studies showed that long non-coding RNAs (lncRNAs) were related to the dysfunction of organs in sepsis. This article aims to screen and validate the sepsis associated lncRNAs and their functional single nucleotide polymorphism (SNPs). Result: The unconditional multiple logistic regression based on the recessive (adjusted odds ratio = 2.026, 95% CI= 1.156-3.551, P=0.0136) showed that patients with CC genotype of rs579501 had increased risk of sepsis. Stratification analysis by age and gender indicated that the patients with rs579501 CC genotype had higher risk of sepsis among children aged < 12 months (adjusted odds ratio = 2.638, 95% CI= 1.167-5.960, P=0.0197) and in males (adjusted odds ratio = 2.232, 95% CI= 1.127-4.421, P=0.0213). We also found the significant relationship between rs579501 and severe sepsis risk (CC versus AA/AC: adjusted odds ratio = 2.466, 95% CI= 1.346-4.517, P=0.0035). Stratification analysis for prognosis and number of organs dysfunction demonstrated that rs579501 CC genotype increased non-survivors’ risk (adjusted odds ratio = 2.827, 95% CI= 1.159-6.898, P=0.0224) and 1-2 organs with dysfunction risk (adjusted odds ratio = 2.253, 95% CI= 1.011-5.926, P=0.0472). Conclusion: Our findings showed that lnc-ZNF33B-2:1 rs579501 CC genotype increased the susceptibility of sepsis. From medicine perspective, lnc-ZNF33B-2:1 rs579501 CC genotype could be serving as a biochemical marker for sepsis.